Emerald Publishing - Come on in, we are OPEN (PUBMET, 2022)
We are passionate about helping authors tell their story in a meaningful and timely way. In doing so, we are committed to providing a leading service for open research, celebrating transparency and co-creation in a way that instils trust and confidence in our communities and global audiences worldwide. We’re passionate about supporting all forms of open research.As a leading social science publisher, we’re passionate about leading change, and align everything we do with the UN’s Sustainable Development Goals. In doing so we publish research that influences thinking, changes policies, and positively makes a difference to lives beyond the walls of academia.